Efektivitas Media AVA dan Leaflet dalam Penyuluhan tentang HIV/AIDS terhadap Peningkatan Pengetahuan Remaja di SMP Negeri 1 Sumpiuh Kabupaten Banyumas Tahun 2011 - Mei Dwi Ismowati; Siti Mulidah; Puji Hastuti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2013)
Media was tools which was used in education. Kinds of media were audio media, visual media for example leaflet and audiovisual media. Audiovisual media had a lot of advantages such as to cover weakness of audio media and visual media. It was more reality and cope with the limited room, time and observation. The purpose of this research was to know the effectiveness of AVA media and leaflet in illumination toward the increase of adolescent knowledge about HIV/AIDS in SMP 1 Sumpiuh Banyumas regency in year 2011. This research used a kind of research true experimental design pretest-post test control group design. Design of the research was cross secsional. The population was all adolescent or all students of SMP 1 Sumpiuh in 2011 about 664 students with 99 students for examples. The way to take sample was using stratified random sampling. To analize the data was using ANOVA. The result of research showed that the average of adolescent knowledge after illumination using AVA media and leaflet got increasing about 9,63%, the adolescent knowledge level got increasing and AVA group had knowledge level good about 36,4%. The conclusion was AVA media was more effective than leaflet in illumination toward adolescent knowledge about HIV/AIDS in SMP N 1 Sumpiuh with increasing 2,90911,87881,000